Slip MHD flow and heat transfer over a nonlinear shrinking surface in a heat generating fluid - Leli Deswita,; Mohd Nazar, Roslinda; Md Ali, Fadzilah; Pop, Ioan (Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Riau, 2012)
In this paper, the problem of steady slip magnetohydrodynamic (MHD) boundary layer flow and heat transfer over a nonlinear shrinking surface in a heat generating fluid is studied. The transformed boundary layer equations are solved numerically using the shooting method. Numerical results are obtained for various values of the magnetic parameter M, the slip parameter K and the transpiration parameter S. The skin friction coefficients, the heat transfer coefficients, the velocity and temperature profiles for various values of parameters are obtained and discussed.